Poorly differentiated high-grade urothelial carcinoma presenting as Paget's disease of the vulva with no overt urinary tract neoplasm detected - Radha R. Padhy; Niloo Nasseri-Nik; Fouad Abbas (Elsevier, 2017)
Objective: There are few reported cases of secondary (non-cutaneous) vulvar Paget's disease related to urothelial carcinoma (UC), with only 7 of them presenting initially with Paget's disease and up to a 13-year lapse from detecting a urinary tract neoplasm after the onset of symptoms. This is a case of Paget's disease of urothelial origin with no urinary tract neoplasm detected on initial presentation. Methods: This is a 59-year-old African-American female who presented with worsening eczematous lesions for two years. She had no symptoms suggestive of UC. Initial biopsies showed poorly differentiated high-grade UC with pagetoid changes. Results: Stains showed immunoreactivity for CK7, uroplakin III, p16 and p63 with negative CK20 expression. This staining pattern is characteristic of pagetoid urothelial intraepithelial lesion, now listed as secondary Paget's disease. Biopsies showed GATTA3 positivity suggestive of urothelial origin. Both GCDFP-15 and CEA were negative, which are normally expressed by Paget cells of the primary (cutaneous) type. A follow-up cystoscopy was unremarkable. The patient underwent a partial radical vulvectomy with bilateral lymphadenectomy for extensive disease. Final pathology confirmed infiltrating high-grade UC with overlying epidermis displaying pagetoid in-situ tumor component. Conclusion: This is a rare case of secondary Paget's disease of urothelial origin where there was no concurrent UC nor did the patient present with symptoms suggestive of a urinary tract malignancy. In initial presentations of vulvar Paget's disease, it is important to be aware of the secondary classification because it warrants investigation of surrounding structures to rule out underlying malignancies that are or have not yet become clinically apparent.